Volume 3: Turbo Expo 2005, Parts a and B 2005
DOI: 10.1115/gt2005-68504
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Application of Roughness Elements to Enhance Heat Transfer in an Impingement Cooling System

Abstract: The inclusion of roughness elements on the target surface of a turbine aerofoil impingement cooling system is an attractive means of heat transfer enhancement. In such a system, it is important to minimise additional pressure loss caused by the roughness elements and thus their shape, size and position need to be optimised. The research showed how heat transfer enhancement is normally achieved at the expense of extra pressure loss. A hexagonal roughness element designed by the authors showed up to 10% heat tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Taslim et al [8] and Son et al [9] confirmed that the roughness elements enhanced the total heat transfer performance of the impingement system with very low pressure penalty when the roughness elements was appropriately located at the low heat transfer coefficient region. Pin-fins have been arranged onto the test surface in an impingement system for its excellent capability of convective heat transfer enhancement.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Taslim et al [8] and Son et al [9] confirmed that the roughness elements enhanced the total heat transfer performance of the impingement system with very low pressure penalty when the roughness elements was appropriately located at the low heat transfer coefficient region. Pin-fins have been arranged onto the test surface in an impingement system for its excellent capability of convective heat transfer enhancement.…”
Section: Introductionmentioning
confidence: 80%
“…Quan et al [10] measured the cooling performance of an impingement system combined with pin fins by using infrared technology, and the overall cooling effectiveness was above 0.8. Funazaki et al [11,12], Son, et al [9] and Yamawaki et al [13] investigated the impingement cooling combined with circular pin fins by using transient liquid crystal technology. Their results showed that the wetted-area averaged Nusselt number of pin-fin roughened target plate was lower than flat plate; however the total heat transfer quantity of the pin-fin roughened plate increased by up to 50%, and the maximum pressure loss only increased by 10%.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the co-flow arrangement, for which the crossflow is parallel to the ribs, is better. Son et al [16,17] investigated the application of roughness elements to enhance heat transfer in an impingement cooling system by conducting flow field and transient heat transfer experiments. The results showed that the roughness elements enhance the total performance of the impingement cooling system with very low pressure penalty.…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that the choice of rib configuration allows altering the local heat transfer distribution significantly, e.g., by shifting the point of maximum heat transfer, and thus allows for a tailoring of local cooling needs. Detailed heat transfer measurements in the form of local distributions were also presented by Son et al [20,21] for different element types. The results showed that the elements enhance total heat transfer performance of the impingement cooling system at low pressure penalty.…”
Section: Introductionmentioning
confidence: 99%